حضرت شیخ بہاء الدین زکریا ملتانیؒ کی سہروردیہ صوفی روایت: بنیادیں، خدمات اور اثرات: Sheikh Bahāūddīn Zakariya Multānīand the Suhrawardī Sufi Tradition: Foundations, Contributions, and Lasting Impact (Al-Qamar, 2025)
Sufism is the relationship with Allah that is performed effectively by Silasil-e-tasawuf. A significant aspect of Sufism is the Suhrawardi Sufi tradition. The founder of Soharwardi tradition, Hazrat Sheikh Shahab al-Din Suhrawardi, provided a framework for it in his book ʿAwarif al-Maʿarif. His disciple, Hazrat Sheikh Bahauddin Zakariya Multani, not only gave this framework a practical shape but also infused Multan with his unique Sufi tradition to such an extent that the city is still remembered as Madinat al-Awliya (the City of Saints). Current study highlights the contours and impact of the Suhrawardi Sufi tradition in Multan. Study founded that based on Suhrawardi philosophy, Hazrat Sheikh Bahauddin Zakariya Multani established the practicality for a Sufi tradition that even after eight centuries later, continues to exist with both continuity and enduring influence.
Keywords: Sufism, Silasil-e-tasawuf, Soharwardi tradition, Awarif al-Maʿarif